Dynamics of Modern and Qur’anic Learning Research (2016–2025) : A Scientometric Mapping Study Using R Biblioshiny - Pitra Gosha Patriasya; Aceng Kosasih; Marwal Blantara Susetyo; Mhd. Aksaril Huda Ritonga; Erwin Putera Permana (PT. Pusmedia Group Indonesia, 2026)
The rapid development of digital technology has profoundly transformed education in the twenty-first century. Nevertheless, modern learning approaches have increasingly been criticized for placing excessive emphasis on technical competencies while overlooking spiritual and moral dimensions. In contrast, Qur’anic learning promotes strong character values and spiritual purification, yet its integration with technological innovation within educational research remains limited and insufficiently systematic. This study aims to examine publication trends, thematic structures, and patterns of scientific collaboration in research on modern and Qur’anic learning during the 2016–2025 period. A bibliometric approach was employed using 136 articles retrieved from the Scopus database. The data were analyzed using R Biblioshiny to generate descriptive, conceptual, and structural mappings. The findings reveal an annual publication growth rate of 45.37%, with an average of 4.603 citations per document. The most frequently occurring keywords in the literature were “e-learning,” “Islamic education,” and “online learning.” Indonesia and Malaysia emerged as the leading contributors to scientific publications, while Universitas Islam Negeri Sunan Kalijaga was identified as the most productive institutional affiliation. The thematic mapping analysis classified “e-learning” as a motor theme, indicating its central role in driving research development within this field. The study concludes that although research productivity expanded substantially following the COVID-19 pandemic, the conceptual integration between modern pedagogy and Qur’anic spiritual values remains fragmented and is still in the consolidation phase. Future studies should strengthen theoretical integration, broaden international research collaboration, and develop integrative learning models capable of balancing global competencies with spiritual maturity grounded in Qur’anic values.